Caracterização mineralógica de diamantes e condições ambientais de formação dos depósitos da região La Candelaria, Município Gran Sabana, fronteira Venezuela-Brasil - Ramirez, Daniel Andres Hernandez (2022)
Diamond is one of several crystallographic modifications of carbon, reflecting its exceptional mechanical hardness and chemical resistance. There are countless applications of the properties of diamonds for the industry in general and for the gems sector. Diamonds occur on the Earth's surface in different types of "primary" (non-sedimentary) rocks: kimberlites, lamproites, and lamprophyres. The objective of the research was to chemically and mineralogically characterize detrital diamonds and their environmental conditions of formation of deposits in the La Candelária region, Gran Sábana Municipality, Venezuela-Brazil border.The study area is located in Santa Elena de Uairén in the area called La Candelaria of the Gran Sabana municipality in the Bolívar state, close to the border between Venezuela and Brazil. The region belongs to the Venezuelan portion of the Guiana Shield, which is located within the limits of the Amazonian Craton, where the Roraima Supergroup is present. In the research, several techniques of characterization and gemological description of diamonds were applied, among them: Scanning Electron Microscopy and Raman Spectroscopy, as well as the description of Shape, Weight, Color, Purity, Dissolution, Cleavage, Impact Marks, Covers and Commercial Qualification. The results showed that the samples presented low granulometry and caratage. In the morphological study, Irregular shaped crystals predominate, followed by octahedron, cube, twin and aggregate. Regarding Color, 31.50% were fancy, 25% yellowish, 23% colorlessyellowish, 10.16% colorless and 10.18% black, with a high degree of dissolution, and mostly without impact marks. Of the samples studied, 34.34% have green spots, 29% yellow spots, 25% without layers and 11.66% green spots. According to their purity, they are non-gemological quality crystals and, commercially, they do not have acceptance for the jewelry industry, however, in the industrial area they could have a good acceptance. The morphological characteristics described indicate a prolonged transport or also those they are subject to several erosive and deposition cycles.